KAJIAN TINJAUAN HUBUNGAN ETNIK DALAM KALANGAN PELAJAR TAHUN SATU DI KAMPUS JOHOR BAHRU, UNIVERSITI TEKNOLOGI MALAYSIA (UTM) - AB RAHMAN, HAMIDAH; AHMAD, NORLIN; NORDIN, NOR AKMAR; MAHMUD, NORASHIKIN; SHAARI, ROZIANAN; ABDUL WAHAB, SHAH ROLLAH (Sains Humanika, 2010)
This research discusses the level of social relation and patriotism among first year students in Johor Bahru Campus, UTM. Respondents of this study were 521 students enrolled in the Ethnic Relation course. A survey method using questionnaire was used. The scopes of the study include social relation from the perspective of ethnic unity and patriotism in the context of love, admiration and loyalty to the country. Data were analyzed using frequency, percentage and mean. The findings showed that the level of social relation among the first year students was at a moderate level, whereas the level of patriotism was high. Several recommendations are given to improve the weaknesses of teaching and learning in Ethnic Relation course at UTM.